510 The importance of noise in the request of early retirement in brazil. (24th April 2018) - Brito, RV; Batalini, VR; Zafalon, AES; Ferreira, LR
Abstract : Introduction: In Brazil, workers exposed to harmful agents are benefited by a public policy denominated Early (Special) Retirement. The main reason for this early retirement is to benefit workers who performed activity that can cause harm to health and include agents such as noise, biological, chemistry, heat, and others. This exposure has to be continuous, permanent and non-intermittent. In this context, due to the large number of companies that expose their workers to noise, the present study aims to analyse the prevalence of noise's requests granted in the request of Early Retirement and characterise the profile of workers who are exposed to this harmful agent. Methods: This was a retrospective study based on the analyses of 118 Profissiographic Profile Documents (PPD), a Brazilian National Social Security document use for granting early retirement for the worker exposed to harmful agents. The research was performed from November 2016 until May 2017, characterising the noise as the main harmful agent for the concession of the early retirement. Results: The noise accounted for 50, 79% of requests for Early Retirement, in addition to 74, 19% of all benefits granted. Considering merely the noise's requests, 44, 74% were accepted. Considering the analysis of gender, 97, 67% of noise's requests were made by men. Furthermore, the more prevalent employment in the analysis were production assistant (26, 07%), production operator (21, 79%) and mechanic (13, 62%). In addition, considering the noise's requests granted, production assistant represented 36, 52%, followed by production operator (27, 83%) and mechanic (4, 35%). Discussion: The study's findings appointed the need for a special attention of government and companies to look for new strategies that aim to reduce the noise intensity in the work environment, especially on the secondary sector (Manufacturing and Industry), contributing for a better occupational health and worker production